Evaluasi Elemen Lanskap Pada Taman Wisata Meuraxa Banda Aceh - M Asrar; B Karsono; S Olivia (Cered Indonesia Institute, 2024)
Tourist parks as public areas for recreation in a city need to have landscape elements that become the attraction of the park. One of the tourist parks in the city of Banda Aceh is Meuraxa Tourist Park, however, in terms of the appropriate use of landscape elements which include softscape and hardscape elements, this is not sufficient. This has an impact on the role and function of landscape elements on the suitability of landscape elements in a park. The aim of this research is to identify landscape elements in Meuraxa Tourism Park and be able to reveal the characteristics, function and suitability of landscape elements. The method used in this research is a qualitative method with descriptive evaluative, using two types of data in the discussion, namely primary data and secondary data. The results of the research show that the appropriate use of softscape elements in the form of plants in the Meuraxa Tourism Park has generally been fulfilled well. However, it is necessary to maintain existing plants. Judging from the hardscape elements, it has not been fulfilled properly and maintenance efforts are needed so that the garden looks orderly.